2009
DOI: 10.1088/0031-9155/54/13/020
|View full text |Cite
|
Sign up to set email alerts
|

PET characteristics of a dedicated breast PET/CT scanner prototype

Abstract: A dedicated breast PET/CT system has been constructed at our institution, with the goal of having increased spatial resolution and sensitivity compared to whole-body systems. The purpose of this work is to describe the design and the performance characteristics of the PET component of this device. Average spatial resolution of a line source in warm background using maximum a posteriori (MAP) reconstruction was 2.5 mm, while average spatial resolution of a phantom containing point sources using filtered back pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 40 publications
1
51
0
Order By: Relevance
“…The measured sensitivities (11.2%; 101.4 cps/kBq) were comparable to or more than twice those of currently available breast PET cameras (3,6,10). This was achieved by the large solid angle of the detector crystals, with a high packing fraction, and the fourth-layer DOI detector (18 mm 5 4.5 · 4).…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…The measured sensitivities (11.2%; 101.4 cps/kBq) were comparable to or more than twice those of currently available breast PET cameras (3,6,10). This was achieved by the large solid angle of the detector crystals, with a high packing fraction, and the fourth-layer DOI detector (18 mm 5 4.5 · 4).…”
Section: Discussionsupporting
confidence: 58%
“…Fully tomographic dedicated PET systems have also been introduced. This type of scanner acquires fully tomographic images by rotating 2 or more planar heads (9)(10)(11) or by completely encircling the breast with detectors (12)(13)(14). Previous simulation studies have shown that, with depth-ofinteraction (DOI) measurement capability, a rectangular tomographic scanner designed to encircle the breast outperforms dual planar designs (with or without DOI) in terms of system sensitivity and image quality (15,16).…”
mentioning
confidence: 99%
“…Systems capable of limited-angle acquisition, such as the positron emission mammography Flex Solo II, also have a compromised ability for radiotracer activity quantification. 14 A high-resolution extremity PET/CT scanner adaptable to wrist and hand imaging was built, 15 and its characterization in conditions typical for patient imaging was reported. 15,16 This system fully produces tomographic images with a spatial resolution of approximately 2.5 mm for the PET component and approximately 0.3 mm for the CT component.…”
Section: Introductionmentioning
confidence: 99%
“…14 A high-resolution extremity PET/CT scanner adaptable to wrist and hand imaging was built, 15 and its characterization in conditions typical for patient imaging was reported. 15,16 This system fully produces tomographic images with a spatial resolution of approximately 2.5 mm for the PET component and approximately 0.3 mm for the CT component. We report-employing prospective imaging data in human patients with established RA and PsA-the ability of this high-resolution PET/CT system to characterize and quantify disease activity and pathology associated with the two arthritides in the wrist and hand.…”
Section: Introductionmentioning
confidence: 99%
“…To find k similar neighbors for each feature vector, a knn search was carried out using the knnsearch function in MATLAB according to Euclidean distance between the feature vectors, not the physical distance among the finite element nodes in the Cartesian coordinates. In this study, three different values of k (16,32,64), the number of nearest neighbors, were studied. Only those elements corresponding to the k-nearest neighbors were kept in the kernel matrix and the rest of them were set to be 0.…”
Section: Kernel-based Anatomically-aided Reconstruction Algorithmmentioning
confidence: 99%